The Right to Rectification and Inferred Personal Data - Häuselmann, Andreas; Custers, Bart (European journal of law and technology, 2024)
Inferred data, such as predictions and emotional states, may have limited accuracy or may even be incorrect from the perspective of data subjects. According to Article 16 of the General Data Protection Regulation (GDPR), data subjects can then invoke their right to rectification. To rectify personal data, data subjects must provide objectively verifiable evidence that the personal data envisaged to replace the data currently processed by the data controller is accurate ('the standard of objective verifiability'). This causes three problems. First, whereas the standard of objective verifiability is easily met for factual data, predictions are not objectively verifiable, mainly because they relate to future conduct or events that have yet to happen (the verifiability problem). Second, the accuracy of subjective personal data, such as emotion data, cannot be proven objectively (the objectivity problem). Third, to effectively rectify inferred personal data, data subjects must be aware that data is inaccurate (the awareness problem). This is often not the case because inferred data are treated as trade secrets and are not shared with data subjects − even when they invoke their right of access.